INVESTIGATION OF FACTORS CAUSING CRACKS IN PRIMARY AIR TUBE BOILERS (CASE STUDY) - Aldony Reco Putra; Muhammad Deddy Syafrullah; Yuliansyah; Muhammad Rizky Tolusha; Nanda Yusril Mahendra (AUSTENIT, 2025)
The primary air tube in the boiler is an important component because it has the function of supplying air that will be used in the combustion process. The reliability of the function of the primary air tube contributes to the quality of the combustion results in the boiler. The purpose of this study is to investigate and analyze the causes of cracks that occur in the primary air tube boiler. The method used in conducting the analysis is using SEM (Scanning Electron Microscope) and microstructure. SEM testing will be used to study the morphology of the crack surface in detail, identify the crack propagation mechanism, and see any indications of corrosion or other elements that may be the cause of damage. Meanwhile, microstructure analysis aims to observe the internal composition of the material to ensure whether there is a structural mismatch that affects the strength and resistance of the material to operational conditions. Based on the test results obtained, there are indications of cracks due to square groove welding found in observations with 100x and 400x magnification only on samples 125 and 126. In the microstructure test with the same sample, indications of cracks were also found that occurred from the outside of the stainless compound due to residual stress and changes in atomic structure at the time of its formation and coupled with the corrosive fuel used, but have not spread to the inner carbon steel material.